P–035 Mathematical model of the signaling cascade during mouse sperm capacitation. (6th August 2021) - Prelle, B. D; Lybaert, P; Gall, D
Abstract: Study question: Modeling the feedback loop controlling sperm capacitation to study the reversibility/irreversibility of the process Summary answer: We demonstrate the existence of a feedback loop between pH increase and hyperpolarization, inducing bistability and possibly the reversibility of the capacitation process. What is known already: The process of mammalian capacitation does need an influx of calcium ions through the transmembrane Catsper Channel Complex. This plasmic membrane channel, which is activated by an increase in either the intracellular pH or the membrane potential, is a sperm-specific protein that is localized in the sperm flagella. Two other sperm specific transporters, sNHE and SLO3, found in the flagella, have been shown to control protons influx and transmembrane voltage respectively, and could work together in a feedback loop keeping the sperm in a high pH state with hyperpolarized membrane. Study design, size, duration: Mathematical model Participants/materials, setting, methods: Not applicable Main results and the role of chance: The results given by this minimal theoretical model are robust as the predicted qualitative behavior can accommodate to a wide span of physiological parameters variations. Limitations, reasons for caution: The model and its parameters are mainly based on in vitro results of the literature, so that the in vivo implications should be inferred carefully. Wider implications of the findings: The possible reversibility of the capacitation process could have major clinical implications, relevant for the optimization of sperm preparation in assisted reproductive techniques and cryopreservation procedures. Trial registration number: Not applicable